Cellular communication through extracellular vesicles and lipid droplets. Issue 3 (1st March 2023) - Amarasinghe, Irumi; Phillips, William; Hill, Andrew F.; Cheng, Lesley; Helbig, Karla J.; Willms, Eduard; Monson, Ebony A.
Abstract: Cellular communication is essential for effective coordination of biological processes. One major form of intercellular communication occurs via the release of extracellular vesicles (EVs). These vesicles mediate intercellular communication through the transfer of their cargo and are actively explored for their role in various diseases and their potential therapeutic and diagnostic applications. Conversely, lipid droplets (LDs) are vesicles that transfer cargo within cells. Lipid droplets play roles in various diseases and evidence for their ability to transfer cargo between cells is emerging. To date, there has been little interdisciplinary research looking at the similarities and interactions between these two classes of small lipid vesicles. This review will compare the commonalities and differences between EVs and LDs including their biogenesis and secretion, isolation and characterisation methodologies, composition, and general heterogeneity and discuss challenges and opportunities in both fields.